A Wholesome Horror: The Stigmas of Leprosy in 19th Century Hawaii - Ron Amundson; Akira Ruddle-Miyamoto (Disability Studies Quarterly, 2010)
The village of Kalaupapa on Moloka'i is well known as the site of legally enforced exile for people in Hawaii with the disease of leprosy. Hawaii was the first nation in the world to institute such a treatment. Less well understood are the social influences that were seen to justify such a harsh treatment of so vulnerable a group of people. Race (and racism) was one influence, as was the fear of contagion. But equally significant was the social stigma produced by Western perceptions of the bodily differences of people with leprosy. Evidence from the Western press shows that the stigma produced by the perceived 'loathsomeness' of the symptoms of leprosy was a prime factor in the exile law. That stigma directly harmed not only people with leprosy, but also their friends and family who supported them.